Important factors in the UNI-Admission Exam - Ordoñez Mercado, Alipio (1998)
In this paper the most important explicative variables in the behaviour of admission exam grades to National Engineering University  is investigated. The tecniques STEPWISE REGRESSION and RIDGE REGRESSION are considerated ans in the analysis is used the results of 1994 admission exam. These data were obtained through sistematic stratificated sampling with proporcional asignation to size population. The results reveals that the most important variable is the general average in high school (XC); others important variables are Admission canal (X1), Pre-University Preparation type (X4), and Pre-University Preparation Time (x7).